2015
DOI: 10.1093/tropej/fmv014
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-pocket nonmedical expenses associated with out-patient treatment of common childhood illnesses

Abstract: Families in rural India have substantial costs incurred in OPD attendance, most of which is for preventive health care such as immunization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
2
4
0
Order By: Relevance
“…Our findings are consistent with the results of other studies reporting that the risk of catastrophic health expenditures was strongly associated with the type of hospitals that patients have access to utilization of healthcare [29]. Our results are consistent with similar findings from another study that showed that the burden of OOP payments was highest among the poor [30], but a high incidence of catastrophic health expenditures has also been found among poor income households [31]. This may reflect the severity of disease in the poor (low-income) groups, which may be greater than in the high-income groups.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are consistent with the results of other studies reporting that the risk of catastrophic health expenditures was strongly associated with the type of hospitals that patients have access to utilization of healthcare [29]. Our results are consistent with similar findings from another study that showed that the burden of OOP payments was highest among the poor [30], but a high incidence of catastrophic health expenditures has also been found among poor income households [31]. This may reflect the severity of disease in the poor (low-income) groups, which may be greater than in the high-income groups.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, to minimize the patients' expenses, Family Health Strategie must prioritize preparing clearer healthcare protocols by defining referral flows, so to meet health demands in a resolute, equitable, and universal strategy. Considering our research backdrop and that food-related direct non-medical costs have been previously reported by other authors 16,17,18 , the public policies should acknowledge our findings, as food is a refundable cost 17 .…”
Section: Discussionsupporting
confidence: 57%
“…conducted a facility based cross-sectional study among children <6 years of age attending the pediatric Outpatient Department (OPD) of a rural nongovernmental medical college in Maharashtra and reported that 36% of the OPD attendance was for respiratory complaints which are higher than that reported in our study. [ 9 ] The different study settings may be a reason for this difference.…”
Section: Discussionmentioning
confidence: 99%
“…61-220), which is lower than our study. [ 9 ] This may be because the medical college provided free OPD services though it was a nongovernmental facility. Therefore, OOP was composed of travel and food charges alone.…”
Section: Discussionmentioning
confidence: 99%